2016
DOI: 10.1152/ajpendo.00425.2015
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming: interaction between prenatal BPA exposure and postnatal adiposity on metabolic variables in female sheep

Abstract: Among potential contributors for the increased incidence of metabolic diseases is the developmental exposure to endocrine-disrupting chemicals such as bisphenol A (BPA). BPA is an estrogenic chemical used in a variety of consumer products. Evidence points to interactions of BPA with the prevailing environment. The aim of this study was to assess the effects of prenatal exposure to BPA on postnatal metabolic outcomes, including insulin resistance, adipose tissue distribution, adipocyte morphometry, and expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 55 publications
5
55
1
Order By: Relevance
“…Our studies in sheep found that prenatal exposure to excess testosterone, a hormone that is also a precursor for estrogen, from days 30 to 90 of gestation leads to low birth weight offspring, reproductive defects, insulin resistance (Padmanabhan and Veiga‐Lopez ) and hypertension (King et al ) thereby establishing the critical window for programming adult reproductive and metabolic defects. Using the same critical window of exposure, our studies also found prenatal BPA treatment at levels found in humans (Padmanabhan et al ) induced insulin resistance and adipocyte hypertrophy (Veiga‐Lopez et al ). Identification of a critical window for programming cardiometabolic dysfunctions in sheep provides a suitable model for testing the developmental impact of BPA exposure.…”
Section: Introductionsupporting
confidence: 69%
“…Our studies in sheep found that prenatal exposure to excess testosterone, a hormone that is also a precursor for estrogen, from days 30 to 90 of gestation leads to low birth weight offspring, reproductive defects, insulin resistance (Padmanabhan and Veiga‐Lopez ) and hypertension (King et al ) thereby establishing the critical window for programming adult reproductive and metabolic defects. Using the same critical window of exposure, our studies also found prenatal BPA treatment at levels found in humans (Padmanabhan et al ) induced insulin resistance and adipocyte hypertrophy (Veiga‐Lopez et al ). Identification of a critical window for programming cardiometabolic dysfunctions in sheep provides a suitable model for testing the developmental impact of BPA exposure.…”
Section: Introductionsupporting
confidence: 69%
“…One epidemiological study reported larger increases in body mass index slope from 2 to 5 years associated with higher BPA with association being stronger in girls, while another found girls exposed to higher concentrations of prenatal BPA have lower body mass index in childhood (Braun et al, ; Harley et al, ). The increased growth rate evidenced in our study may contribute to the insulin resistance and increase in adipocyte size and inflammatory markers evidenced in adult prenatal BPA‐treated sheep (Veiga‐Lopez et al, ). The implication of the initial slower trajectory of postnatal weight gain followed by increased weight gain velocity later in males needs to be explored further, as several other factors such as environmental exposure to other ubiquitously present environmental chemicals and their interaction with diet could also be playing a role.…”
Section: Discussionmentioning
confidence: 51%
“…In rodent models, prenatal BPA has been shown to lead to insulin resistance in the male offspring (Alonso‐Magdalena et al, ). Our group has previously shown that female offspring exposed to prenatal BPA also develop reduced insulin sensitivity in adulthood (Veiga‐Lopez et al, ). To our knowledge, this is the first study to assess insulin sensitivity in fetal circulation at early and later gestation in both sexes.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Bisphenol A has been shown in epidemiological studies to be associated with increased risk of obesity, and it has also been shown to have direct effects on adipose tissue development (adipogenesis) along with pancreas development and function, leading to an obese, insulin-resistant phenotype 3133. Similarly, phthalates have also been associated with an increased risk of obesity due to their direct effects on liver function (hepatic fat accumulation) and their ability to disrupt thyroid function (dysregulation of energy balance and metabolism) 3436…”
Section: Environmental Chemical Exposures During Pregnancy and The Dementioning
confidence: 99%